A Reversed Trend: Care for Limited English Proficiency Patients in the Pediatric Emergency Department - Murray, Brittany; Gillepsie, Scott E.; Levine, Alyssa; Greenky, David (Emergency medicine international, 2019)
Objectives. Previous studies in pediatric emergency departments (EDs) showed patients with limited English proficiency (LEP) had gaps in care compared with English-speaking patients. In 2010, the Joint Commission released patient-centered communication standards addressing these gaps. We evaluate the current care of LEP patients in the Children’s Healthcare of Atlanta (CHOA) EDs. Methods. This was a retrospective cohort study of patients <18 years that presented to our EDs in 2016. Length of stay (LOS), change in triage status, return-visit rates, and hospital disposition were compared between patients who requested an interpreter and those who did not. Results. The population included 152,945 patients from 232,787 ED encounters in 2016. Interpreters were requested for 12.1% of encounters. For ED LOS, a model-adjusted difference of 0.77% was found between interpreter groups. For change in triage status, adjusted odds were 7% higher in the interpreter requested cohort. For ED readmission within 7 days, adjusted odds were 3% higher in the interpreter requested cohort. These effect sizes are small (ES < 0.2). Conclusions. Our study showed low ES of the differences in ED metrics between LEP and English-speaking patients, suggesting little clinical difference between the two groups. The impact of this improvement should be further studied.